2022
DOI: 10.1083/jcb.202203045
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of secretory, endosomal, and autophagic routes in trans-Golgi–associated lysosomes

Abstract: At the trans-Golgi, complex traffic connections exist to the endolysosomal system additional to the main Golgi-to–plasma membrane secretory route. Here, we investigated three hits in a Drosophila screen displaying secretory cargo accumulation in autophagic vesicles: ESCRT-III component Vps20, SNARE-binding Rop, and lysosomal pump subunit VhaPPA1-1. We found that Vps20, Rop, and lysosomal markers localize near the trans-Golgi. Furthermore, we document that the vicinity of the trans-Golgi is the main cellular lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 112 publications
1
11
0
Order By: Relevance
“…To circumvent copper‐induced toxicity, this type of direct transport ensures faster response in elevated copper conditions. A recent study has shown that TGN‐associated lysosome acts as a hub for secretory, endosomal, and autophagic routes in drosophila 52 . Interestingly, we found that an increase in TGN46‐LAMP2 colocalisation is positively correlated with copper‐induced endolysosomal localisation of ATP7B that increases with increasing copper (Figure 5A,B).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…To circumvent copper‐induced toxicity, this type of direct transport ensures faster response in elevated copper conditions. A recent study has shown that TGN‐associated lysosome acts as a hub for secretory, endosomal, and autophagic routes in drosophila 52 . Interestingly, we found that an increase in TGN46‐LAMP2 colocalisation is positively correlated with copper‐induced endolysosomal localisation of ATP7B that increases with increasing copper (Figure 5A,B).…”
Section: Resultssupporting
confidence: 57%
“…A recent study has shown that TGN-associated lysosome acts as a hub for secretory, endosomal, and autophagic routes in drosophila. 52 Interestingly, we found that an increase in TGN46-LAMP2 colocalisation is positively correlated with copper-induced endolysosomal localisation of ATP7B that increases with increasing copper (Figure 5A,B). We further explored if these TGN-proximal lysosomes serve as a 'distribution hub' for endolysosomal dispersal (trafficking) of ATP7B in elevated copper.…”
Section: Tgn-proximal Lysosomes Serve As a Hub For Endolysosomal Sort...mentioning
confidence: 77%
“…To circumvent copper-induced toxicity, this type of direct transport ensures faster response in elevated copper condition. A recent study has shown that TGN associated lysosome acts as a hub for secretory, endosomal and autophagic route in drosophila (Zhou et al, 2023). Interestingly, we found that increase in TGN46-LAMP2 colocalisation is positively correlated with copper-induced endolysosomal localisation of ATP7B that increases with increasing copper (fig 5A, 5B).…”
Section: Resultsmentioning
confidence: 99%
“…The early or sorting endosomes are thought to be maintained by the continuous transport of vesicles from the plasma membrane and TGN (Grant & Donaldson, 2009). However, recent studies suggest that vesicles emerging from TGN and not from plasma membrane are indispensable for the formation of RAB5 + endosomes (Nagano et al, 2019; Zhou et al, 2023). Additionally, RAB5 is suggested to regulate the process of endo‐lysosomal trafficking from TGN (Grant & Donaldson, 2009; Nagano et al, 2019; Woodman, 2000; Zhou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that vesicles emerging from TGN and not from plasma membrane are indispensable for the formation of RAB5 + endosomes (Nagano et al, 2019; Zhou et al, 2023). Additionally, RAB5 is suggested to regulate the process of endo‐lysosomal trafficking from TGN (Grant & Donaldson, 2009; Nagano et al, 2019; Woodman, 2000; Zhou et al, 2023). The colocalization of G1P3 with RAB5, TGN, and lysosomal markers suggests the trafficking of G1P3 from TGN into endolysosomes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%